Combined Catheter Ablation and Left Atrial Appendage Closure in Atrial Fibrillation Patients with and without Prior Stroke - Bin-Feng Mo; Rui Zhang; Jia-Li Yuan; Jian Sun; Peng-Pai Zhang; Wei Li; Mu Chen; Qun-Shan Wang; Yi-Gang Li (Journal of Interventional Cardiology)
Background. Combined atrial fibrillation (AF) ablation and left atrial appendage closure (LAAC) has been practiced for management of both the symptoms and the high stroke risk of AF. Data of the combined procedure in selected patients with prior stroke are limited. The aim of this study is to compare the safety and efficacy of combined catheter ablation and LAAC between AF patients with and without prior stroke. Methods and Results. This retrospective study enrolled 296 patients who underwent combined procedures of AF ablation and LAAC. Patients were divided into two groups: 81 patients with prior stroke (Stroke group) and 215 patients without prior stroke (Control group). Combined procedures were successfully performed in all the patients. Patients in the Stroke group had higher CHA2DS2-VASc scores (4.9 ± 1.2 vs. 3.2 ± 1.0, P<0.001) and higher HAS-BLED scores (3.5 ± 1.1 vs. 3.0 ± 1.0, P<0.001) compared with those in the Control group. Procedure-related complications in the Stroke group included two pericardial effusions and two groin hematomas, which did not differ significantly fromthe Control group (4.9% vs. 4.2%, P=0.778). After a mean follow-up of 20 months, the AF-free rate of the Stroke group was comparable with that of the Control group (64.2% vs. 68.4%, P=0.495). The relative risk reductions in stroke and bleeding (observed rate compared to that predicted from the CHA2DS2-VASc and HAS-BLED scores) were 80% and 79%, respectively, in the Stroke group, and 62% and 62%, respectively, in the Control group. Conclusions. The combination of catheter ablation and LAAC is safe and efficient in selected AF patients with prior stroke. It was observed that patients with prior stroke may benefit more from risk reductions of stroke and bleeding following the combined procedure.